Mindfulness is associated with intrinsic functional connectivity between default mode and salience networks - Doll, Anselm; Hölzel, Britta K.; Boucard, Christine C.; Wohlschläger, Afra M.; Sorg, Christian (Frontiers in Human Neuroscience, 2015)
Mindfulness is attention to present moment experience without judgment. Mindfulness practice is associated with brain activity in areas overlapping with the default mode, salience, and central executive networks (DMN, SN, CEN). We hypothesized that intrinsic functional connectivity (i.e. synchronized ongoing activity) across these networks is associated with mindfulness scores. After two weeks of daily 20-minutes attention to breath training, healthy participants were assessed by mindfulness questionnaires and resting-state functional MRI. Independent component analysis of imaging data revealed networks of interest, whose activity time series defined inter-network intrinsic functional connectivity (inter-iFC) by temporal correlation. Inter-iFC between subnetworks of the DMN and SN - and inter-iFC between subnetworks of the SN and left CEN at trend - was correlated with mindfulness scores. Additional control analyses about visual networks’ inter-iFC support the specificity of our findings. Results provide evidence that mindfulness is associated with intrinsic functional connectivity between default mode and salience networks. Data suggest that ongoing interactions among central intrinsic brain networks link with the ability to attend to current experience without judgment.